Association between 8 P‐glycoprotein (MDR1/ABCB1) gene polymorphisms and antipsychotic drug‐induced hyperprolactinaemia; British Journal of Clinical Pharmacology; Vol. 86, iss. 9 - Geers L. M.; Pozhidaev I. V. Ivan; Ivanova S. A. Svetlana Aleksandrovna; Freydin M. B. Maksim Borisovich; Schmidt A. F. Amand; Cohen D.; Boyko A. S.; Paderina D. Z. Diana; Fedorenko O. Yu. Olga Yurievna; Semke A. V.; Bokhan N. A. Nikolay Aleksandrovich; Wilffert B. Bob; et al. (2020, 2020)
Title screen